On the Philosophy of Probability Behaviour Composite Probability Æ¤(P) In the Case of Discrete Function - Jughaiman, Abdulaziz (European Scientific Journal, ESJ, 2023)
This paper is dealing with probability theory, starting from an objectivism philosophic approach, towards mathematical approach. This approach is aiming to study the probability behaviour as a function and as a fraction quantity. This aim, is requiring a discussion of the usage of the probability statement, the causes behind the existence of probabilistic phenomenon, and an explanation that admits to measure the causality by probability theory, through the concept of conditioning and the concept of compliment. This paper is using conceptual experiment with a design that addresses the shortcoming of traditional conceptual experiment. Also, it is using the relative frequency of event and the probability axioms. These, in turn will reflect some aspects of the probabilistic behaviour, in addition to some important consequences that follow from. As a result this will provide a sample space to include all possible events in the form of sequence of sub sequences. Also, this paper will provide some definitions that define some elements of the fractions probabilities and the sample space. These are beside, some proven corollaries that admit to calculate composite probability in the case of discrete function. In addition, to a briefly treatment to the continuous function.